Development of A Kahoot Application-Based Module In NKPI Courses To Improve Student's Learning Interest In SMKN 2 Rembang - Sukristiyo, Sukristiyo; Samsudi, Samsudi; Utanto, Yuli (Innovative Journal of Curriculum and Educational Technology, 2022)
Implementation in the learning process in the Covid 19 pandemic era at SMKN 2 Rembang showed a decrease in learning achievement due to lack of student interest in learning, this is based on a survey of researchers at the end of the semester showing that the average value of students decreased from 2020 during remote/online learning. This study aims to develop a teaching material based on Kahoot evaluation to increase students' interest in learning. This study uses the RnD research method with the ADDIE model consisting of analysis, design, development, implementation and evaluation. The results of the material validation carried out obtained an average of the three aspects of material validation (feasibility of the material, presentation and language) which was 4.26 and was in the "very good" criteria. Likewise with the results of product validation, the average of the three aspects of the validation of teaching/media materials (display, presentation, and effectiveness) is 4.4 and has the criteria of "very good". Furthermore, the results of students' interest in learning from the categories of feeling happy, students' attention, interest in student learning and aspects of involvement were also in the very good category.